Insect-specific virus platforms for arbovirus vaccine development - Roy A. Hall; Roy A. Hall; Wilson Nguyen; Alexander A. Khromykh; Alexander A. Khromykh; Andreas Suhrbier; Andreas Suhrbier (Frontiers in Immunology)
Certain insect-specific viruses (ISVs), specifically the mosquito alphaviruses, Eilat and Yada Yada viruses, and orthoflaviviruses, Binjari, Aripo, YN15-283-02 and Chaoyang viruses, have emerged as potential platforms for generation of whole virus vaccines for human and veterinary applications. These ISVs are remarkably tolerant of the substitution of their structural polyproteins with those of alphaviruses and orthoflaviviruses that are pathogenic in humans and/or animals. The resulting ISV-based chimeric vaccines have been evaluated in mouse models and have demonstrated safety and efficacy in non-human primates, crocodiles and pigs. Targets include chikungunya, Venezuelan and eastern equine encephalitis, dengue, Zika, yellow fever, Japanese encephalitis and West Nile viruses. ISV-based chimeric vaccines provide authentically folded tertiary and quaternary whole virion particle structures to the immune system, a key feature for induction of protective antibody responses. These vaccines are manufactured in C6/36 or C7-10 mosquito cell lines, where they grow to high titers, but they do not replicate in vertebrate vaccine recipients. This review discusses the progress of these emerging technologies and addresses challenges related to adjuvanting, safety, and manufacturing.